Single-Junction Polymer Solar Cells Exceeding 10% Power Conversion Efficiency - Chen, Jing-De; Cui, Chaohua; Li, Yan-Qing; Zhou, Lei; Ou, Qing-Dong; Li, Chi; Li, Yongfang; Tang, Jian-Xin (Advanced materials (Weinheim), 2015)
A single‐junction polymer solar cell with an efficiency of 10.1% is demonstrated by using deterministic aperiodic nanostructures for broadband light harvesting with optimum charge extraction. The performance enhancement is ascribed to the self‐enhanced absorption due to collective effects, including pattern‐induced anti‐reflection and light scattering, as well as surface plasmonic resonance, together with a minimized recombination probability.